2016
DOI: 10.1590/1983-21252016v29n203rc
|View full text |Cite
|
Sign up to set email alerts
|

'Packham's Triumph' Pear Response to 1- Methylcyclopropene and Nitric Oxide Treatments

Abstract: -This study aimed at assessing the effect of 1-methylcyclopropene (1-MCP), gas-nitric oxide (NO) and sodium nitroprusside (SNP) on ripening of 'Packham's Triumph' pears. The treatments consisted of T 1 ) control; T 2 ) 300 ppb 1-MCP; T 3 ) 1 mM SNP; T 4 ) 10 ppm NO; and T 5 ) 20 ppm NO. The fruit treated with 1-MCP showed significantly higher values for flesh firmness, texture, and peel green color, besides lower respiratory rates and ethylene production. On the other hand, NO and SNP treatments did not reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Flesh firmness maintenance can be explained by the lower ethylene production of the fruit in 1 μl/L NO applied daily and 5 μl/L NO applied every 5 days of CA storage. Other studies have also demonstrated the effectiveness of NO in maintaining the flesh firmness of different fruit types, which is related to lower ethylene production and lower activity of cell wall enzymes (Gergoff et al, 2017; Hendges et al, 2016; Singh et al, 2009; Sun et al, 2011). In banana, the application of NO showed higher flesh firmness and reduced the activity of the enzymes pectinmethylesterase, polygalacturonase, and endo‐β‐1,4‐glucanase (Cheng et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Flesh firmness maintenance can be explained by the lower ethylene production of the fruit in 1 μl/L NO applied daily and 5 μl/L NO applied every 5 days of CA storage. Other studies have also demonstrated the effectiveness of NO in maintaining the flesh firmness of different fruit types, which is related to lower ethylene production and lower activity of cell wall enzymes (Gergoff et al, 2017; Hendges et al, 2016; Singh et al, 2009; Sun et al, 2011). In banana, the application of NO showed higher flesh firmness and reduced the activity of the enzymes pectinmethylesterase, polygalacturonase, and endo‐β‐1,4‐glucanase (Cheng et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In 'Galaxy' apples there was also no observed effect of the application of NO on the maintenance of flesh firmness after storage (Brackmann et al 2017). However, in 'Feicheng' peaches (Sun et al 2011;Zhu et al 2006), ' Amber Jewel' plums (Singh et al 2009) and 'Packhams Triumph' pears (Hendges et al 2016), NO treatment led to higher flesh firmness after storage. This divergence of results between studies could be due to the different species of fruit, as well as to the experimental procedures adopted.…”
Section: Nitric Oxide (Concentrationmentioning
confidence: 87%
“…A higher h° value in the apple skin represents less yellow coloration, which indicates a lower degree of matureness, since the skin color is a trustworthy indicator of fruit maturation (Saure 1987). In 'Packhams Triumph' pears, a lower degree of yellowing of the skin was observed following the application of NO (Hendges et al 2016). The lower h° value observed in the fruit control group after 70 days of storage and plus 7 days of shelf life visually indicated more mature fruit.…”
Section: Nitric Oxide (Concentrationmentioning
confidence: 99%
“…Eth dose was defined based on preliminary tests (unpublished data). The doses of NO evaluated were established based on the results obtained in other fruits (Hendges et al., 2016; Singh et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…For the treatments with NO, the gas (NO 1,000 µl L −1 + N 2 balance) was added to the interior of the hermetic mini‐chambers until pre‐established concentrations were achieved (10 and 20 µl L −1 ), with exposure for 2 hr in an environment with 1 kPa of O 2 + ≤0.1 kPa of CO 2 and 20 ± 3°C (Hendges et al., 2016).…”
Section: Methodsmentioning
confidence: 99%